2015 ESC GUIDELINES FOR THE DIAGNOSIS AND MANAGEMENT OF PERICARDIAL DISEASES - Yehuda Adler; Philippe Charron; Massimo Imazio; Luigi Badano; Gonzalo Barón-Esquivias; Jan Bogaert; Antonio Brucato; Pascal Gueret; Karin Klingel; Christos Lionis; Bernhard Maisch; Bongani Mayosi; et al. (Российский кардиологический журнал)
The Task Force for the Management of Infective Endocarditis of the European Society of Cardiology (ESC)Endorsed by: European Association for Cardio-Thoracic Surgery (EACTS)